ÉVALUATION FORMATIVE PAR LE BIAIS DE PRATIQUES « LERNEN DURCH LEHREN » DESTINÉES AUX ÉTUDIANTS DE NIVEAU AVANCÉ - Widła, Halina (Neofilolog, 2020)
This article illustrates ways of assessing students’ work in the Multimedia master’s seminar and compares the benefits of formative and summative evaluations in this context. During the Multimedia seminar, prospective foreign language teachers and translators create their own multimedia resources, which fill a gap in teaching materials on offer. This allows the students to become specialists in particular areas. This article illustrates ways of assessing students’ work in the Multimedia master’s seminar and compares the benefits of formative and summative evaluations in this context. Students appreciated the importance of formative assessment, recognizing its advantage over summative evaluation. Systematic semi-autonomous work subjected to continual verification proved to be key to the achievement of the desired skills. The results also demonstrated how knowledge of learners’ first and second languages is advantageous, as it allows teachers to more accurately identify and evaluate the difficulties learners face during the acquisition of a third language. These unusual forms of learning by teaching require considerable time and sufficient motivation but notably improve the quality of the learning process.